Alexander and the terrible, horrible, no good, very bad day - Viorst, Judith; Cruz, Ray (New York : Aladdin Books, 1987)
On a day when everything goes wrong for him, Alexander is consoled by the thought that other people have bad days too. Alexander wakes up to a bad day & things get progressively worse as the hours wear on, until he thinks he may escape it all & go to Australia. On a day when everything goes wrong for him, Alexander is consoled by the thought that other people have bad days too. Alexander knew it was going to be a terrible day when he woke up with gum in this hair. And it got worse ... His best friend deserted him. There was no dessert in his lunch bag. And, on top of all that, there were lima beans for dinner and kissing on TV!
Keywords: Humorous stories -- Juvenile literature; Humorous stories; Humorous stories; Juvenile works